Shigella in Africa: New Insights From the Vaccine Impact on Diarrhea in Africa (VIDA) Study. (19th April 2023) - Kasumba, Irene N; Badji, Henry; Powell, Helen; Hossain, M Jahangir; Omore, Richard; Sow, Samba O; Verani, Jennifer R; Platts-Mills, James A; Widdowson, Marc-Alain; Zaman, Syed M A; Jones, Jennifer; Sen, Sunil; et al.
Abstract: Background: We evaluated the burden of Shigella spp from children aged 0–59 months with medically attended moderate-to-severe diarrhea and matched controls at sites in Mali, The Gambia, and Kenya participating in the Vaccine Impact on Diarrhea in Africa (VIDA) study from 2015 to 2018. Methods: Shigella spp were identified using coprocultures and serotyping in addition to quantitative polymerase chain reaction (qPCR). Episode-specific attributable fractions (AFe) for Shigella were calculated using Shigella DNA quantity; cases with AFe ≥0.5 were considered to have shigellosis. Results: The prevalence of Shigella was determined to be 359 of 4840 (7.4%) cases and 83 of 6213 (1.3%) controls by culture, and 1641 of 4836 (33.9%) cases and 1084 of 4846 (22.4%) controls by qPCR (cycle threshold <35); shigellosis was higher in The Gambia (30.8%) than in Mali (9.3%) and Kenya (18.7%). Bloody diarrhea attributed to Shigella was more common in 24- to 59-month-old children (50.1%) than 0- to 11-month-old infants (39.5%). The Shigella flexneri serogroup predominated among cases (67.6% of isolates), followed by Shigella sonnei (18.2%), Shigella boydii (11.8%), and Shigella dysenteriae (2.3%). The most frequent S . flexneri serotypes were 2a (40.6%), 1b (18.8%), 6 (17.5%), 3a (9.0%), and 4a (5.1%). Drug-specific resistance among 353 (98.3%) Shigella cases with AMR data was as follows: trimethoprim-sulfamethoxazole (94.9%), ampicillin (48.4%), nalidixic acid (1.7%), ceftriaxone (0.3%), azithromycin (0.3%), and ciprofloxacin (0.0%). Conclusions: A high prevalence of shigellosis continues in sub-Saharan Africa. Strains are highly resistant to commonly used antibiotics while remaining susceptible to ciprofloxacin, ceftriaxone, and azithromycin. Abstract : We evaluated the burden of Shigella spp from children 0–59 months with medically attended moderate-to-severe diarrhea and matched controls at sites in Mali, The Gambia, and Kenya participating in the Vaccine Impact on Diarrhea in Africa study from 2015 to 2018.